The Impact of Anticipatory Governance on Crisis Management Preparedness and Disaster Risk Reduction in the United Arab Emirates - ALHAJERI, NOURA ABDELAZIZ (2024)
Anticipatory governance has been identified as an important approach allowing organizations to foresight, plan and prepare for the future. However, while crisis and disaster are dynamic and changing, the current approach to existing crisis management practices focuses on occurrence and post-occurrence of disasters as opposed to a more preventive pre-crisis management approach. Against this backdrop, this research investigates the impact of anticipatory governance on crisis management preparedness in the UAE. To be precise, the study uncovers the indirect effect of anticipatory governance on preparedness and disaster risk reduction via a crisis management lens. To address this aim, a quantitative methodology is adopted based on 214 senior management participants working in crisis management departments from different entities in the UAE. Using a structural equation modelling approach, the findings of the research revealed that anticipatory governance can contribute to the attainment of key priorities of the Sendai Framework for disaster risk reduction through crisis management activities. In particular, the culture element of anticipatory governance was found to be the strongest element of anticipatory governance shaping crisis management for disaster risk reduction, followed by feedback and foresight. In contrast, the network element was noted to have a trifle role. The current research is novel as it bridges the research-acknowledged paucity in the literature on the interconnection between anticipatory governance and crisis management, notably in the UAE. From a practical point of view, the primary implication is to critically consider pre-crisis anticipation through the adoption and appreciation of anticipatory governance as an important tool in crisis management preparedness and foster a better awareness and anticipation for the reduction and mitigation of disaster risks.